Tortious Liability for Defective Products in the People’s Republic of Chin - Epstein, Edward J. (Columbia Journal of Asian Law, 1988)
The traditional preoccupation of China’s leaders with gross industrial output has long compromised economic efficiency and product quality. Official consternation at socialist industry’s failure to meet expected quality standards already accompanied “socialist trans- formation” as early as the 1950s, but it was not until 1978 that the State Council, following directions from the Party, prohibited statisti- cians from including products which do not meet state standards in the annual figures for industrial output. Thenceforth, statisticians have set apart the proportion of products which do not meet state standards. Generally, there has been a proportional decrease in the number of substandard products, but this is not always the case. It is alarming that even official statistics show the quality score of many industrial products, especially consumer products, to be low and fall- ing. There is special cause for concern since, in 1987, China’s rural industrial output exceeded agricultural output for the first time.